Abnormal Lipid Profile in Fast-Growing Broilers With Spontaneous Femoral Head Necrosis - Fan, Rubin; Liu, Kangping; Zhou, Zhenlei (Frontiers in Physiology, 2021)
This study investigated lipid metabolism in broilers with spontaneous necrosis of femoral head (FHN) by determining the levels of markers of the blood biochemistry and bone metabolism. According to the femoral head score of 3th, 4th and 5th week old chickens affected with FHN, the birds were divided into normal group and FHN group, and a comparative study was conducted. It showed that the lipid metabolism was disorder in spontaneous FHN broilers while hyperlipidemia occurred, and the accumulation of lipid droplets in femur was observed. In addition, there were significant changes in bone parameters and blood bone biochemistry markers (BALP and TRACP), genes expressions related to lipid metabolism (PPAR γ and LRP1) in the femoral head also increased significantly. Therefore, FHN may be resulted from dyslipidemia affecting bone growth and development in broilers.